Advances in XML information retrieval and evaluation revised selected papers - Fuhr Norbert ed.; International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2005; International workshop of the initiative for the evaluation of XML retrieval, INEX 2005 Dagstuhl Castle, Germany 28-30 Nov 2005 (Berlin Springer-Verlag, 2006)
This book constitutes the thoroughly refereed post-proceedings of the 4th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2005, held at Dagstuhl Castle, Germany, in November 2005. The papers are organized in topical sections on methodology, multiple retrieval, ad-hoc retrieval, relevance feedback, natural language queries, heterogeneous retrieval, interactive retrieval, document mining, and multimedia retrieval.
Keywords: Electronic data processing; XML (Document markup language)